Education on the Introduction of a Good Nutritional Intake Balance in Canteen Snacks and Staple Foods for Elementary School Students - Denisa Nur Ramadhanti Yamin; Asep Bayu Dani Nandiyanto (Publikasi Indonesia, 2022)
This study aims to educate early recognition of a good balance of nutritional intake in canteen snacks and staple foods for students at Tugu Elementary School, Cihideung Village, Parongpong District, West Bandung Regency, Indonesia. The age range of the respondents is 8-10 years. Respondents consist of 7 boys and 12 girls. This method is carried out by knowing in advance the knowledge of students with a pre-test which was held on July 19, 2022 for 4th grade students of SD Tugu who were immediately given socialization of educational materials about balanced nutrition such as the importance of good nutrition balance. tumpeng (TGS), 10 Guidelines for Balanced Nutrition, The importance of bringing lunch from home, and reducing plastic waste, then after that do a post-test and question and answer. The results of the study: The provision of good nutrition balanced education with lecture methods and PPT media was proven to be effective in increasing the level of knowledge, attitudes and habits of elementary school students which was proven through post-test and question and answer sessions during the presentation. Conclusion: Education on balanced nutrition through the lecture method and using power point media is quite effective in increasing the understanding and awareness of Tugu Elementary School students about balanced nutrition, as well as sorting out intake and good snacks for students.